Open Oral Food Challenge in Adult with Food Allergy to Chicken Meat - Yosi Charly; Cita Rosita SP; Trisniartami Setyaningrum (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Food allergy is a hypersensitivity of the body's response to food. Food allergies are divided into three groups: immunoglobulin E (IgE) mediated, non-IgE mediated, and mixed IgE mediated with non-IgE mediated. Food allergies can be life threatening, causing malnutrition, eating disorders, and psychosocial problems. The gold standard for the diagnosis of food allergy is double-blind placebo-controlled food challenge (DBPCFC), but time consuming, costly, and a resuming specialist to perform it. Open oral food challenge (OFC), commonly used as screening in the clinic, with food suspected of being in its true form, in particular to look for symptoms. Objective: To evaluate specific IgE and open OFC in adult patients with a history of food allergies to chicken. Methods: Descriptive cross-sectional study involving 28 adult patients with history of food allergies to chicken were diagnosed as urticaria, angioedema, and atopic dermatitis. Specific IgE chicken meat was performed and patients were asked to eliminate chicken for 1 week before open OFC. Results: Twenty eight samples, specific IgE within normal limit. Positive results of open OFC were found in 9 people and 19 negative result. Conclusion: The specific IgE chicken does not always correlate with clinical reactivity and open the OFC can be used for the diagnosis of food allergy to chicken meat. Key words: food allergies, spesific Ig E, open oral food challenge.